Influence of dental implant designs on stress distribution and micromotion of mandibular bone / Muhammad Saiful Islam Mohd Izra'ai - Mohd Izra'ai, Muhammad Saiful Islam (2018)
The significant effects of biomechanical dental implant designs have been realised by some researchers, however, the studies were restricted on the discrete invariability of designs and geometries of dental implants on the primary stability of immediately loaded implants. Moreover, restricted procedure and limited software ability to develop a comprehensive 3D model of mandibular bone make the in vitro studies on dental implants relatively unreliable. This research was conducted to provide a feasible method for reconstructing the 3D model of mandibular bone to undergo finite element analysis. This study also examines several design features of dental implants based on commercially available products. Then, the highest performance dental implant design was evaluated, and the significant design parameters were studied in order to determine the optimal combination of design parameters. Computerised Tomography scan was conducted to generate head images for bone reconstruction process. MIMICS software 8.0 and 3-matic software were used to develop the 3D mandibular model. The reconstructed mandibular model was then assembled with five different 3D models of dental implants. Feasible boundary conditions and material properties were assigned to the developed muscle areas and joints. The results of the maximum von Mises stresses, shear stresses and deformations were analysed, and the best design was selected. Next, grey based Taguchi method was used to identify several design parameters influences such as conical hollow height, thread thickness, cutting-edge angle and cutting-edge depth. The second model appeared to exhibit the highest performance in this bone remodelling prediction simulation. Lastly, the optimal combination of design parameters calculated in this study were 5 mm of conical hollow height, 0.3 mm of thread thickness, 30° of cutting-edge angle and 6 mm of cutting-edge depth. In conclusion, this research provides a systemic approach to develop segmented 3D mandibular bones with quality meshing in order to prevent error in finite element analysis. Based on this study, the suggested optimal combination had improved the dental implant and bone performance.